A qualitative study exploring self-directed learning in a medical humanities curriculum - Walser, Sarah; Gary, Mercer; Stephens, Mark B (Research and Humanities in Medical Education, 2022)
Introduction: The humanities enrich and transform the practice of medicine. What remains to be seen, however, is how best to integrate humanities into the medical curriculum to optimize both educational and patient-related outcomes. The present study considers the structure of an innovative student-driven humanities curriculum and seeks to understand its strengths and limitations, as well as make recommendations for improvement. Methods: The Penn State College of Medicine, University Park Regional Campus uses an inquiry-based approach to education, whereby students are responsible for creating learning objectives in four core pillars of exploration: Foundational Science, Clinical Science, Health Systems Science, and Health Humanities. This study explores student-derived humanities learning objectives (HLO) across four years of the curriculum. Results: 420 HLOs met criteria for analysis and were coded as instrumental (developing direct clinical skill), non-instrumental (non-skill based), or both. Of these, 125 (30%) were instrumental, 239 (57%) were non-instrumental, and 56 (13%) were coded as both. Most instrumental HLO centered around communication skills. Non-instrumental HLO most commonly focused on bearing witness and critiquing a particular experience within a social and/or political context. Conclusions: Findings from this study contribute to the development of a humanities curriculum in a student-directed learning program. Non-instrumental HLO lacked a theoretical framework to guide student’s investigations to a deeper level of analysis. Student-directed learning offers many strengths, but can be enhanced through external direction from humanities trained faculty, particularly given that many medical students have a limited humanities background.